Influence of vegetation heterogeneity and landscape characteristics on anuran species composition in aquatic habitats along an urban-rural gradient in southeastern Brazil - Oda, Fabrício Hiroiuki; Gonçalves, Sidnei; Oda, Thiago Massao; Tschope, Lara Carolina Raphael; Briso, André Luiz Fraga [UNESP]; Oliveira, Marcelo Rodrigues Freitas; Takemoto, Ricardo Massato; Vasconcelos, Tiago Silveira [UNESP] (Nature Research Centre -NRC, 2017)
Amphibians are exposed to a number of negative factors in urban areas and the influence of a specific variable can vary among different ecological systems. This study provides information on the anurofauna along an urban-rural gradient in Araçatuba, São Paulo State, Brazil. Anurans were sampled in 11 breeding habitats distributed throughout seven surveyed sites in urban, peri-urban and rural areas, during six field visits between May 2011 and January 2013. We recorded 23 species of anurans belonging to 12 genera and four families. For both urban and peri-urban regions, we recorded 11 species per area, the number of species in the rural area reaching 20. The greatest similarity in species composition found at urban and peri-urban sites showed the urbanization-induced impoverishment and homogenization of their anuran communities. In contrast, the anurofauna of the rural area was rich and diversified. Vegetation heterogeneity in breeding habitats and forest formations surrounding these water bodies was found to have a positive effect on species richness and composition and, therefore, to be an important factor affecting amphibian populations in water bodies in urban, peri-urban and rural areas.
Keywords: Amphibians; anthropic disturbance; conservation; inventory; vegetation heterogeneity